A Sudden Change of Plans? Reassessing the Hospitallers’ Crusading Strategy in the Early Fourteenth Century - Wallmeyer, Gion (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2025)
The loss of the Crusader States in the late thirteenth century sparked a multitude of projects in the West to recover the Holy Land, with the Templars and Hospitallers at the forefront of the enterprise. Several of the plans drawn up during this period have survived in written form, allowing historians to trace the evolution of Western crusader strategy. Among these innovations was the plan for a multi-stage crusade, set out in a brief French memorandum by the Hospitallers, which historians have dated to 1306–1309. Recent scholarship has challenged this assessment, suggesting a later date for the memorandum because the project differs from the orders’ other recovery plans of the time. The article re-examines these arguments by looking at the manuscript evidence as well as parallel sources from royal and papal registers. It argues for the thesis that the memorandum was composed for Pope Clement V between March and August 1308 and that it was inextricably linked with the Hospitallers’ plans to conquer Rhodes. On this basis, the deviations noted by historians should be seen as the result of changing geopolitical circumstances and a rapidly evolving expert discourse at Western courts.